[Book Review]: Reimagining Scholarship in Higher Education—A Review of Sam Illingworth’s Bridging Scholarship and Practice in Higher Education - Abrahamson, Earle (Teaching and Learning Inquiry, 2025)
Review of Bridging Scholarship and Practice in Higher Education by Sam Illingworth.